DECISION-MAKING TOOL FOR A CONSTRUCTIVE RELATION BETWEEN EMBLEMATIC FACILITIES AND URBAN REGENERATION PROJECTS APPLIED TO THE CASE OF RIAD EL FETH ARTS CENTRE IN ALGIERS - Bouallag-Azoui, Ouafida; Berezowska-Azzag, Ewa (Quaestiones Geographicae, 2019)
Considered as a lever for urban regeneration politics, the construction of emblematic facilities is also a way to enhance metropolitan attractiveness. The Algerian capital is no exception to this rule. These new urban icons are designed to be the catalysts of urban change, and are expected to improve the adaptation of metropolitan localities to new needs and developmental challenges. However, in the field, this iconic regeneration does not always bring the expected changes. The Riad El Feth Arts Centre, an iconic facility located in the central municipality of El Madania in Algiers, is one example. In this paper we propose an operational tool called EFLUR (Emblematic Facilities Leverage of Urban Regeneration), intended to facilitate urban decision-making by evaluating the leverage of emblematic facilities at targets of urban strategy. It helps to assesses and optimise their leverage capacity by identifying their failures and opportunities, with a view to undertaking necessary actions, both to amplify positive contamination and to limit detrimental effects. The Riad El Feth is selected as a study case to validate our approach and test the operationality of EFLUR. Beyond conventional impact studies, the value of this tool lies in its holistic approach and capacity to combine metropolitan objectives with local development strategies.